PENGARUH KEPEMILIKAN ASING DAN LEVERAGE TERHADAP KINERJA KEUANGAN - Sari, Rafika (Universitas Muhammadiyah Palembang, 2020)
The purpose of this study is to determine and analyze the effect of Foreign Ownership and Leverage Effects on Financial Performance in Manufacturing Companies Listed on the Indonesia Stock Exchange (IDX) Period 2014 - 2018 The results of this study simultaneously Fcount value of 5.808 with a probability of 0.04 smaller than 0.05 so it can be concluded that all independent variables (Foreign ownership and leverage) together have a significant effect on financial performance. Changes that occur in financial performance can be explained by the variable Foreign ownership and leverage of 73%, the remaining 27% is explained by other variables outside the model. partially foreign ownership has a significant positive effect on financial performance with a coefficient of t count 3.004 and a significance of 0.003. Debt Equity Ratio variable has a significant negative effect on financial